Differential transformation and antibacterial effects of silver nanoparticles in aerobic and anaerobic environment - Dong, Feng (2021)
Silver nanoparticles (AgNP) undergo various transformations into different Ag species in the environment, which determines their toxicity in microorganisms. In aerobic condition, AgNPs release Ag⁺ that causes cell inactivation. Limited information is known about the AgNP-cell interaction in oxygen-free environment. Here we compared the transformation and antibacterial effects of AgNPs in aerobic and anaerobic environment. The bacterium Pseudomonas aeruginosa was relatively not susceptible to Ag⁺ or AgNP in anaerobic environment, indicated by near two orders of magnitude greater of anaerobic minimum inhibitory concentration (MIC) than the aerobic counterpart. In anaerobic environment, the dissolved Ag concentration decreased due to the reduction of Ag⁺. Electron microscopy images showed the formation of new AgNPs and aggregates, preferably on cell surface or associated with extracellular polymer substances (EPS) matrix. Accumulating AgNPs onto the cells could cause membrane damage, cytoplasm release or bacterial death. Meanwhile, EPS and cell lysate were very likely to bind AgNPs, facilitating the extensively assembling of AgNPs into large aggregates. This reduced the effective Ag exposure to cells and might contribute to the detoxification in anaerobic environment. Further, flow cytometry analysis quantified that bacterial membrane was largely intact under the treatment of AgNPs in anaerobic condition compared to the dose-response manner in aerobic condition.